Conversational Recommender Systems Based on Criticism for Tourist Attractions using TF-IDF - Rayhan M Auliarahman; Z K Abdurahman Baizal; Nurul Ikhsan (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Tourist attractions are one of the attractions of tourist interest. There are many types of tourist attractions in an area, but this becomes a problem in itself because tourists will find it hard to find or determine a tourist attractions that suit their tastes. Many researches on recommendation systems based on criticism have been carried out with the aim of obtaining user preferences. However, only a few studies have conducted a critique-based recommendation system using the Conversational Recommender System (CRS). With this research, we will discuss a recommendation system based on criticism using natural language or CRS for tourist attractions in Bandung. In this study, we add assistance from the system to help users choose preferences or what can be called System-suggested Critiques (SC), users more easily determine preferences for the system. We use the Term Frequency-Inverse Document Frequency (TF-IDF) to determine critiques submitted to users. Based on the results of an evaluation involving 88 respondents who were asked to fill out a questionnaire after trying the system built, it was found that users were quite satisfied with the system we built. And obtained 62.06% system accuracy which proves that the system performance is quite satisfactory.